Quality and cost-effectiveness in long-term care and dependency prevention: the Polish policy landscape - Stanisława Golinowska; Agnieszka Sowa-Kofta (Center for Social and Economic Research (CASE), 2017)
With the population ageing the development of sustainable long-term care institutions is of great importance in many European countries. In Poland, currently dominant, traditional and family based care will become insufficient with increasing cohorts of older people. Presented paper discusses recent developments in long-term care policy in the country. Long-term care institutions are separated in the two sectors, with little field for cooperation and coordination of activities. Over the past years policy addressing ageing related problems was developed, focusing on the active ageing instruments. Dependency prevention and active ageing are among goals of national policies formulated separately in the health and social sector. Information policy and monitoring long-term care services' provision remains insufficient. Coordination of activities mainly takes place at the local level. Local governments and non-governmental organizations, often cooperating with representatives of older people, are active in providing services to older people in community and often incorporating innovative solutions in care.
Keywords: I10; I18; I31; I38; 330; long-term care policy; long-term care institutions; informal care; dependency prevention; ageing; older people